2014
DOI: 10.1371/journal.pone.0109725
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Apical Fluid-Regulating Channel Proteins with Lung Function in Human COPD Lungs

Abstract: Links between epithelial ion channels and chronic obstructive pulmonary diseases (COPD) are emerging through animal model and in vitro studies. However, clinical correlations between fluid-regulating channel proteins and lung function in COPD remain to be elucidated. To quantitatively measure epithelial sodium channels (ENaC), cystic fibrosis transmembrane conductance regulator (CFTR), and aquaporin 5 (AQP5) proteins in human COPD lungs and to analyze the correlation with declining lung function, quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…This was also confirmed in the lower airways [7]. In these studies, CFTR dysfunction was tightly associated with symptoms of chronic bronchitis [5,7], and was positively correlated with reduced forced expiratory volume (FEV 1 ) in the lungs of patients with COPD [8]. …”
Section: Acquired Cftr Dysfunction In Smoking-related Diseasesmentioning
confidence: 90%
“…This was also confirmed in the lower airways [7]. In these studies, CFTR dysfunction was tightly associated with symptoms of chronic bronchitis [5,7], and was positively correlated with reduced forced expiratory volume (FEV 1 ) in the lungs of patients with COPD [8]. …”
Section: Acquired Cftr Dysfunction In Smoking-related Diseasesmentioning
confidence: 90%
“…In recent years, cystic fibrosis transmembrane conductance regulator (CFTR) as a drug target in some major diseases has been gaining increasing attention. The latest clinical research has found that the expression of the ion channel protein CFTR can decrease significantly in patients with COPD [6]. This finding indicates that CFTR may be related to the pathogenesis of COPD.…”
Section: Introductionmentioning
confidence: 95%
“…Over-activation of ENaC by airway-targeted βENaC overexpression leads to the generation of concentration gradient of sodium ions (e.g., sodium ions going from outside to inside of the cell) followed by over-absorption of water into the cells, which results in dysregulated airway mucus production and airway clearance59. Based on the lines of evidence showing that the expression and function of ENaC were inversely associated with lung function in CF patients910 and could be augmented in COPD patients1112, βENaC-Tg mice could be valuable tools for exploring mucus obstructive phenotypes of COPD and CF in vivo . However, the mortality of βENaC-Tg mice with a mixed C3H/HeN:C57/BL6N background was extremely high5, which limits usage of the original βENaC-Tg line as an animal model of acute and fulminant airway diseases.…”
mentioning
confidence: 99%